Développement de la vidéo touristique bilingue de la ville de Semarang comme source d’information pour les touristes francophones - Aullia Salsabila; Neli Purwani (Universitas Negeri Semarang, 2026)
Indonesia is an archipelagic country rich in ethnic, cultural, and linguistic diversity. Semarang City, located in Central Java, reflects this richness through its unique blend of Javanese, Chinese, and Dutch cultural influences. While Semarang holds strong potential in cultural and historical tourism, its promotion remains limited, especially among French-speaking tourists. According to 2023 data from the Semarang Department of Culture and Tourism, the number of francophone visitors is still low compared to those from the Netherlands and China. One of the main challenges identified is the lack of promotional media for tourism in French. This study uses the Research and Development (R&D) method to develop a bilingual (French Indonesian) tourism promotional video. The product is designed to meet the information needs of French-speaking tourists and enhance Semarang’s appeal as a cultural and historical destination. The conclusion of this research highlights the importance of bilingual promotional videos to effectively attract and inform francophone tourists.